FDI and Growth in East Asia: Lessons for Indonesia - Robert E. Lipsey; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2010)
Foreign direct investment has been important in the economic growth and global economic integration of developing countries over the last decades. Both Northeast and Southeast Asia, especially the latter, have been part of this development with increasing inflows of FDI and greater foreign participation in their economies. However, Indonesia has been an outlier within the region, with lower inflows of FDI than other countries, especially in manufacturing, and with lower inflows than could be expected from its size and other country characteristics. The inflows of FDI that have taken place have benefited Indonesia and we use the Asian experience to provide some suggestions as to what measures would increase FDI. A relatively poor business environment with inefficient institutions seems to be an important explanation behind the low inflows of FDI.
Keywords: F13; F23; O19; 330; East Asia; Northeast Asia; Southeast Asia; Indonesia; Foreign Direct Investment; Multinational Firms; Direktinvestition; Multinationales Unternehmen; Außenhandelspolitik; Wirtschaftsförderung; Indonesien; Asien (Nordost); Südostasien